Modified silicas, methods for their preparation and use thereof

CN115867512BActive Publication Date: 2026-10-16EVONIK OPERATIONS GMBH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202180048368.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-07
Filing Date
2021-07-05
Publication Date
2026-10-16
Estimated Expiration
2041-07-05

AI Technical Summary

Benefits of technology

[0088] The advantages of the modified silica according to the invention are that the corresponding rubber mixtures have reduced Mooney viscosity and extended processing window, thereby improving processability. Furthermore, the rubber mixtures according to the invention exhibit improved dynamic properties and improved elongation at break, as well as equivalent tensile strength, dispersion quality, and abrasion resistance of the vulcanized products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115867512B_ABST
    Figure CN115867512B_ABST
Patent Text Reader

Abstract

The invention provides a modified silica having the following physico-chemical parameters: mixing silica with at least one additive selected from the group consisting of an aqueous thiolalkoxysilane emulsion, a polysiloxane, a mixture of a thiolalkoxysilane and a polysiloxane, or a mixture of a thiolalkoxysilane and an anionic polyether at the inlet of a drying unit, and then feeding the mixture to the drying unit, to produce a modified silica. The modified silica is used to produce pneumatic tires, cable sheaths, hoses, drive belts, conveyor belts, roll covers, tires, shoe soles, gasket elements and damping elements.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention relates to modified silica, its preparation method, and its uses.

[0002] E.F. Vansant, P. Van der Voort, K. C. Vancken, Characterization and chemical modification of the silica surface, Chemical Studies in Surface Science and Catalysis Vol. 93, Elsevier Verlag, 1995, discloses the chemical modification of silica using various reagents such as organosilanes (pp. 194-198; 266-270; 288-292).

[0003] The hydrophobication of precipitated silica is also known from DE 10138491 A1 and DE 10138492 A1, in which it is directly added to the dryer. There is also a conditioning step.

[0004] WO2014033300 A1 discloses the use of dicarboxylic acid to modify precipitated silica.

[0005] A known drawback of modified silica is the increased viscosity of the mixture, leading to poorer processing of the rubber compound. Furthermore, this is accompanied by a narrowing processing window and a tendency for premature crosslinking, which complicates the preparation process. Another disadvantage of pretreatment is its adverse effect on dynamic properties and poorer filler dispersion in the vulcanized material.

[0006] The object of this invention is to provide a modified silica that, compared with in-situ silanization or in-situ modification, exhibits improved processing characteristics and dynamic properties of the mixture. Furthermore, the modified silica has equivalent or improved filler dispersion quality.

[0007] This invention provides modified silica, characterized by having the following physicochemical parameters:

[0008]

[0009] The Ro-Tap value of the modified silica at >150 μm according to the present invention can be 80%, preferably >85%.

[0010] The Ro-Tap value of the modified silica at >300 μm according to the present invention can be 50%, preferably >60%.

[0011] The Ro-Tap value of the modified silica at >500 μm according to the present invention can be 20%, preferably >40%.

[0012] The DOA absorption of the modified silica according to the present invention can be 100-300 ml / (100 g), preferably 140-240 ml / (100 g).

[0013] The drying loss of the modified silica according to the present invention can be <4.5% by weight, preferably 2.0-4.0% by weight.

[0014] The pH value of the modified silica according to the present invention can be ≥6.3, preferably 6.3-8.0.

[0015] TAR of modified silica according to the present invention mod The value can be >1%, preferably 15-70%.

[0016] The calcination residue of the modified silica according to the present invention can be 70-95%, preferably 80-95%.

[0017] The IF value of the modified silica according to the present invention, obtained by pressurized Hg pore size determination, can be... Preferred

[0018] The IS value of the modified silica according to the present invention, obtained by pressure Hg pore size determination, can be ≤79 ml / (100 g), preferably 50-79 ml / (100 g).

[0019] The PV value (V80, 3.7-80nm, 140°) of the modified silica according to the present invention can be ≤0.86ml / g, preferably 0.30-0.86ml / g.

[0020] The modified silica according to the present invention can be fumed silica or precipitated silica, preferably precipitated silica.

[0021] The present invention also provides a method for preparing modified silica according to the invention, characterized in that silica is mixed with at least one additive selected from the following at the inlet of a drying unit: an aqueous sulfur-containing alkoxysilane emulsion, a polysiloxane such as preferably polydimethylsiloxane and its side-chain modified derivatives, a mixture of sulfur-containing alkoxysilane and polydimethylsiloxane, and a mixture of sulfur-containing alkoxysilane and anionic polyether, and then supplied to the drying unit.

[0022] Preliminary mixing has already taken place at the inlet, unlike DE 10138491 A1 and DE 10138492 A1, where the additives are added directly to the dryer. Furthermore, in this invention, the subsequent conditioning steps described in DE 10138491 A1 and DE 10138492 A1 are unnecessary.

[0023] The modified silica can be used without further conditioning.

[0024] The inlet can be a conveying screw, preferably a twin screw, and more preferably a non-meshing twin screw.

[0025] BET of silica used in the method according to the present invention MP The surface area can be 50-300 m² 2 / g, preferably 80-280m 2 / g. The CTAB surface area of ​​silica can be 40-280m². 2 / g, preferably 70-260m 2 / g.

[0026] Silica can be fumed silica or precipitated silica, with precipitated silica being preferred.

[0027] Sulfur-containing alkoxysilanes can be alkoxysilanes of formula (I).

[0028] [(RO)3Si-R 3 -] n A (I)

[0029] Wherein R may be the same or different, and is a straight-chain unsubstituted or branched unsubstituted (C1-C10) alkyl group, preferably (C1-C6) alkyl, more preferably methyl or ethyl, or alkyl polyether-(R 1 -O) m -R 2 , where R 1 The same or different, and whether branched or unbranched, saturated aliphatic divalent C1-C30 hydrocarbon groups, with m averaging 1 to 30, R 2 It is an unsubstituted branched or unbranched monovalent C1-C30 alkyl, C2-C30 alkenyl, C6-C30 aryl, or C7-C30 aralkyl group, R 3 It is a branched or unbranched, saturated or unsaturated, aliphatic, aromatic or mixed aliphatic / aromatic divalent C1-C30 hydrocarbon group, n=1 or 2, when n=2, A is S x x = 1 - 10, and when n = 1, A is SH, SCN or SC(O)R.

[0030] The sulfur-containing alkoxysilane is preferably a bis[(3-triethoxysilyl)propyl] disulfide or (EtO)3Si-(CH2)3-SC(O)-C7H 15 .

[0031] The aqueous sulfur-containing alkoxysilane emulsion may be an emulsion of an alkoxysilane of formula (I).

[0032] The aqueous sulfur-containing alkoxysilane emulsion is preferably a bis[(3-triethoxysilyl)propyl] disulfide emulsion. The aqueous sulfur-containing alkoxysilane emulsion used may be 50% by weight of bis[(3-triethoxysilyl)propyl] disulfide or bis[(3-triethoxysilyl)propyl] polysulfide emulsion, having <0.5% by weight of a nonionic surfactant.

[0033] The polysiloxane may be modified or unmodified polydimethylsiloxane. Modified polydimethylsiloxane may contain polyether phosphate groups, alkyl ester groups, or polyether groups. The polysiloxane used may be a polyether siloxane.

[0034] The mixture of sulfur-containing alkoxysilane and polydimethylsiloxane may contain 0.1-50% by weight of polydimethylsiloxane.

[0035] The mixture of sulfur-containing alkoxysilane and anionic polyether may contain 0.1-50% by weight of polyether.

[0036] The polyether may be an anionic modified polyether; for example, the polyether may contain phosphate groups.

[0037] The drying unit can be a Henschel mixer or a rotary flash dryer.

[0038] The reaction in the Henschel mixer can be carried out at temperatures of 80°C–170°C, preferably 95°C–145°C.

[0039] The reaction in the rotary flash dryer can be carried out at an outlet temperature of 70°C-180°C, preferably 80°C-170°C.

[0040] The initial distribution of the additives is not carried out by simultaneous drying as described in DE 10138492 A1, but rather at the inlet upstream of the dryer. This can be accomplished, for example, by a high-shear, meshing twin-screw dryer.

[0041] The weight ratio of silica to additives can be 100:1-100:15, preferably 100:3-100:10, and more preferably 100:4-100:8.

[0042] The present invention also provides a rubber compound comprising

[0043] (A) Rubber or rubber mixture, and

[0044] (B) At least one modified silica according to the present invention.

[0045] The rubber used can be natural rubber and / or synthetic rubber. Preferred synthetic rubbers are described, for example, in W. Hofmann, Kautschuktechnologie [Rubber Technology], Genter Verlag, Stuttgart 1980. They may include:

[0046] - Polybutadiene (BR)

[0047] - Polyisoprene (IR),

[0048] - Styrene / butadiene copolymers, such as emulsion SBR (E-SBR) or solution SBR (S-SBR), preferably with a styrene content of 1%-60% by weight, more preferably 5%-50% by weight (SBR).

[0049] -Chloroprene (CR),

[0050] -Isobutylene / isoprene copolymer (IIR),

[0051] - Butadiene / acrylonitrile copolymer, wherein the acrylonitrile content is 5%-60% by weight, preferably 10%-50% by weight (NBR).

[0052] - Partially hydrogenated or fully hydrogenated NBR rubber (HNBR),

[0053] - Ethylene / propylene / diene copolymer (EPDM)

[0054] The aforementioned rubber also possesses functional groups such as carboxyl, silanol, or epoxy groups, for example, epoxidized NR, carboxyl-functionalized NBR, or silanol (-SiOH)- or silanoxy (-Si-OR)-functionalized SBR.

[0055] And mixtures of these rubbers.

[0056] In a preferred embodiment, the rubber can be vulcanized with sulfur. For the manufacture of automotive tire treads, anionic polymeric S-SBR rubber (solution SBR) with a glass transition temperature above -50°C, and mixtures thereof with butadiene rubber, are particularly preferred. S-SBR rubber in which the vinyl content of the butadiene component exceeds 20% by weight is particularly preferred. S-SBR rubber in which the vinyl content of the butadiene component exceeds 50% by weight is particularly preferred.

[0057] A mixture of the above-mentioned rubbers can preferably be used, wherein the S-SBR content is more than 50% by weight, preferably more than 60% by weight.

[0058] The rubber compound according to the invention may contain other fillers. The following fillers may be used as fillers in the rubber compound according to the invention:

[0059] - Carbon black: Carbon black can be prepared by lampblacking, furnace blackening, gas blackening, or heat treatment, and its surface area is 20 to 200 m². 2 / g. Carbon black may also optionally contain heteroatoms, such as Si.

[0060] - Amorphous silica, for example, prepared by precipitation from silicate solution or by flame hydrolysis of silicon halides, having a specific surface area of ​​5 to 1000 m². 2 / g, preferably 20 to 400m 2 / g (BET surface area), with a primary particle size of 5 to 400 nm. Silica may also optionally be in the form of a mixed oxide with other metal oxides such as Al oxide, Mg oxide, Ca oxide, Ba oxide, Zn oxide, and titanium oxide, and / or contain trace amounts of up to 10,000 ppm of these metal ions.

[0061] - Synthetic silicates (such as aluminum silicate) and alkaline earth metal silicates (such as magnesium silicate or calcium silicate) have a BET surface area of ​​20 to 400 m². 2 / g, with primary particle diameters ranging from 10 to 400 nm.

[0062] - Synthetic or natural aluminum oxides and synthetic or natural aluminum hydroxide.

[0063] - Natural silicates, such as kaolin and other naturally occurring silica.

[0064] - Glass fiber and glass fiber products (pads, threads) or glass microspheres.

[0065] Amorphous silica prepared by precipitation from silicate solution, having a BET surface area of ​​20 to 400 m², can be preferred. 2 / g, more preferably 100m 2 / g to 250m 2 / g, which is in amounts of 5 to 150 parts by weight, each based on 100 parts of rubber.

[0066] The filler can be used alone or in the form of a mixture.

[0067] The rubber mixture may contain 5 to 150 parts by weight of modified silica according to the invention, and 0.1 to 20 parts by weight, preferably 1 to 18 parts by weight, more preferably 5 to 15 parts by weight of organosilane, wherein the parts by weight are based on 100 parts by weight of rubber.

[0068] The rubber mixture may also contain silicone oil and / or alkylsilanes. The rubber mixture may also contain resins, modified resins, and / or reactive resins.

[0069] The rubber mixtures according to the invention may contain other known rubber additives, such as crosslinking agents, vulcanization accelerators, reaction accelerators, reaction retarders, antioxidants, stabilizers (including aging stabilizers), processing aids, plasticizers, waxes or metal oxides, and optionally activators such as triethanolamine, polyethylene glycol or hexanetriol.

[0070] Rubber additives can be used in conventional amounts, depending on factors including the end use. Conventional amounts can be, for example, based on 0.1% to 50% by weight of the rubber.

[0071] The crosslinking agent used can be sulfur or an organic sulfur donor.

[0072] The rubber compound according to the invention may contain other vulcanization accelerators. Examples of suitable vulcanization accelerators that may be used include mercaptobenzothiazoles, sulfinamides, guanidines, dithiocarbamates, thioureas, thiocarbonates, and zinc salts of these, such as zinc dibutyldithiocarbamate.

[0073] The rubber compound according to the present invention may further comprise:

[0074] Thiuram sulfide accelerators and / or carbamate accelerators and / or corresponding zinc salts,

[0075] Nitrogen-containing co-activators,

[0076] Other optional rubber additives, and

[0077] Other optional promoters may be present.

[0078] The weight ratio of the accelerator to the nitrogen-containing co-activator can be equal to or greater than 1.

[0079] The rubber compound according to the invention may contain at least 0.25 parts by weight of tetrabenzylthiuram disulfide or tetramethylthiuram disulfide based on 100 parts by weight of rubber, and at most 0.25 parts by weight of diphenylguanidine, cyclohexylsulfinamide or dicyclohexylsulfinamide based on 100 parts by weight of rubber.

[0080] It is preferable to use sulfinamide with guanidine and thiuram together, and more preferably to use cyclohexylsulfinamide or dicyclohexylsulfinamide with diphenylguanidine and tetrabenzylthiuram disulfide or tetramethylthiuram disulfide together.

[0081] Depending on the rubber used, the amount of vulcanization accelerator and sulfur can be from 0.1% to 10% by weight, preferably from 0.1% to 5% by weight. Sulfur and sulfinamides are particularly preferred in amounts of 1% to 4% by weight, thiurams in amounts of 0.2% to 1% by weight, and guanidines in amounts of 0% to 0.5% by weight.

[0082] The present invention also provides a method for preparing a rubber mixture according to the invention, characterized in that rubber or a rubber mixture, modified silica according to the invention, and other optional rubber additives are mixed in a mixing unit.

[0083] The blending of rubber with fillers, any rubber additives, and the modified silica according to the invention can be carried out in commonly used mixing units, such as rollers, closed mixers, and mixing extruders. This type of rubber blend can typically be prepared in a closed mixer by first mixing the rubber, fillers, the modified silica according to the invention, and the rubber additives at 100°C to 170°C in one or more consecutive thermomechanical mixing stages. The order and timing of the addition of the individual components can have a critical impact on the final properties of the blend. Typically, the resulting rubber blend can be mixed with crosslinking chemicals in a closed mixer or roller at 40°C to 110°C, and the blend can be treated to obtain a so-called coarse blend for subsequent steps of the process, such as molding and vulcanization.

[0084] Rubber blends can be used in masterbatch form and / or through continuous mixing processes. Rubber blends can be prepared via methods known as liquid-phase mixing or continuous liquid-phase mixing, or through the combination of masterbatches.

[0085] The rubber compound according to the invention can be vulcanized at a temperature of 80°C to 200°C, preferably 130°C to 180°C, and optionally at a pressure of 10 to 200 bar.

[0086] The rubber compound according to the invention can be used to prepare molded articles by vulcanization.

[0087] The rubber compound of the present invention can be used to prepare molds, for example, for preparing pneumatic tires, cable sheaths, hoses, drive belts, conveyor belts, roller covers, tires (especially tire treads), shoe soles, sealing elements such as sealing rings and damping elements, etc.

[0088] The advantages of the modified silica according to the invention are that the corresponding rubber mixtures have reduced Mooney viscosity and extended processing window, thereby improving processability. Furthermore, the rubber mixtures according to the invention exhibit improved dynamic properties and improved elongation at break, as well as equivalent tensile strength, dispersion quality, and abrasion resistance of the vulcanized products.

[0089] Test method:

[0090] CTAB - CTAB surface area determined according to ISO 5794-1-G

[0091] This method is based on the adsorption of buffered CTAB (N-hexadecyl-N,N,N-trimethylammonium bromide) in aqueous solution onto an "outer" surface of silica, also known as a "rubber-active surface." The unadsorbed CTAB is back-titrated using NDSS (sodium dioctyl sulfosuccinate solution). The titration endpoint is the point of maximum increase in solution opacity.

[0092] This procedure conforms to ISO 5794-1G, and its descriptions, additions, and deviations are as follows:

[0093] • In the sample preparation process, it is preferable to use a suitable grinder to ultrafine grind coarse-grained silica and silicate samples, or to pulverize them using a mortar and pestle and then sieve them through a 90 μm sieve, rather than pulverizing them using a mortar and pestle and then grading them using a 150 μm sieve as described in the standard.

[0094] • The test sample and the expected CTAB surface area are less than 200m² 2 A suspension consisting of CTAB solution of / g was stirred for 10 minutes. As described in the standard, the test sample and the expected CTAB surface area of ​​not less than 200m² were used. 2 A suspension consisting of / g CTAB solution was stirred for 35 minutes.

[0095] • After adsorption, the silica is filtered through a 0.2μm polyamide filter.

[0096] • The filtrate was titrated using a Metrohm titration processor equipped with an autosampler and a Tirando 809. The photometric electrode used was a Metrohm Spectrosense 523nm.

[0097] CTAB mod-The CTAB value of ethanol – CTAB – is determined according to ISO 5794-1-G. mod.

[0098] This method is based on the adsorption of buffered CTAB (N-hexadecyl-N,N,N-trimethylammonium bromide) in an aqueous ethanol solution onto a hydrophobic silica "outer" surface, also known as a "rubber-active surface." The unadsorbed CTAB is back-titrated using NDSS (sodium dioctyl sulfosuccinate solution). The titration endpoint is the point of maximum increase in solution opacity.

[0099] This procedure conforms to ISO 5794-1G, and its descriptions, additions, and deviations are as follows:

[0100] • In the sample preparation process, it is preferable to use a suitable grinder (e.g., IKA M20 grinder) to ultrafine grind coarse-particle silica and silicate samples, or to pulverize them with a mortar and pestle and sieve them through a 75 μm sieve, rather than pulverizing them with a mortar and pestle and grading them with a 150 μm sieve as described in the standard.

[0101] • To determine the blank value of the NDSS solution used, transfer 5.00 ml of the mixture of (30.0±0.1) ml CTAB solution, (10.0±0.1) ml ethanol, and 55 ml softened water into a titration beaker.

[0102] Weigh the fractionated sample material to an accuracy of 0.1 mg and place it in a 50 ml centrifuge tube equipped with a magnetic stir bar, pre-wetting it with 10.0 ml of ethanol. Then add (30.0 ± 0.1) ml of CTAB solution and stir with a magnetic stirrer for 20-25 minutes (for expected CTAB values ​​greater than 200 mg). 2 For samples of / g, the time is 35-40 minutes.

[0103] • The solid and liquid phases were separated after adsorption by centrifugation at at least 4000 rpm and RCF 2500 for 15 minutes.

[0104] • Liquid chromatography was titrated using a Metrohm titration processor equipped with an autosampler and a Tirando 905. The photometric electrode used was a Mettler-Toledo DP5, operating at a wavelength of 555 nm.

[0105] BET MP - Nitrogen BET surface area determined according to DIN ISO 9277

[0106] According to DIN ISO 9277, this method is used to determine the N2 specific surface area of ​​silica by the BET method. In this method, the measurement is performed by adsorbing nitrogen gas at a specified partial pressure at a low temperature. The analysis was conducted as a multi-point determination, and with a total of 5 measurement points, it showed almost linear behavior in the partial pressure range (p / po) of 0.05–0.2.

[0107] This procedure conforms to DIN ISO 9277 and the following instructions:

[0108] Before weighing, carefully crush the particulate sample with a scraper, and then degas it for 60 minutes at (160±2)℃ using a Micromeritics Vac Prep061 vacuum degassing thermostat.

[0109] To determine the BET surface area, the following five relative pressure points (p / po) were recorded during the adsorption phase: 0.0500; 0.0875; 0.1250; 0.1625 and 0.2000.

[0110] For measurement purposes, a static volumetric test method was used with a Dewar container from the TriStar 3000 series (3000 / 3020 / 3030) of MICROMERITICS.

[0111] Carbon content – ​​determined according to DIN EN ISO 3262-19

[0112] The determination was performed using LECO elemental analyzers (instrument types CS-200 and CS-600) and an external evaluation unit (PC with LECO software) in accordance with DIN EN ISO 3262-19.

[0113] Weigh the sample and place it in a ceramic crucible. Add an oxidation catalyst and combustion promoter (e.g., LECO's Lecocel II) and an inducer (e.g., LECO's ultrapure iron turnings). Combust the sample in the induction oven of the elemental analyzer. The carbon in the sample is oxidized to CO2 in an oxygen stream. Quantification of the gas is performed by infrared detection. For the operation, maintenance, and adjustment of the analyzer, refer to the guidelines and instructions in LECO's operating manual.

[0114] Calibration should be performed using BAM steel standards 289-1, 130-1, and 283-1. Standards and starting weights should be selected to ensure the sulfur content of the test sample is within the calibration range. Calibration is completed by calculating a calibration line containing at least four calibration points.

[0115] Sulfur content - Total sulfur - Determined according to DIN EN ISO 3262-19 or ASTM D 6741 Method B for silica test samples.

[0116] a. Determination method for unmodified silica

[0117] The determination was performed using LECO elemental analyzers (instrument types CS-200 and CS-600) and an external evaluation unit (PC with LECO software) in accordance with DIN EN ISO 3262-19.

[0118] Weigh the sample and place it in a ceramic crucible. Add an oxidation catalyst, a combustion promoter (e.g., LECO's Lecocel II), and an inducer (e.g., LECO's ultrapure iron filings). Combust the sample in the induction oven of the elemental analyzer. Sulfur in the sample is oxidized to SO2 in an oxygen stream. Quantification of the gas is performed by infrared detection. For the operation, maintenance, and adjustment of the analyzer, refer to the guidelines and instructions in LECO's operating manual.

[0119] Calibration should be performed using BAM steel standards 289-1, 130-1, and 283-1. Standards and starting weights should be selected to ensure the sulfur content of the test sample is within the calibration range. Calibration is completed by calculating a calibration line containing at least four calibration points.

[0120] b. Determination method for modified silica

[0121] Sulfur content was determined using a LecoSC-144DR total sulfur analyzer. Samples were burned in an oxygen stream at 1350°C; the resulting SO2 was quantified using an infrared measurement unit. This method conforms to ASTM D 6741 Method B.

[0122] During the determination, weigh the test sample and calibrator into an evaporating dish, then push the evaporating dish into the combustion tube of the sulfur analyzer. For liquid calibrator and sample, cover the bottom of the evaporating dish with approximately 2g of sea sand before weighing the sample. Cover the weighed sample with another portion of sea sand (approximately 1g). The amounts of calibrator and sample should be selected and matched so that the weighed amount is within the range of 0.1-0.2g as much as possible. The sample weight should be approximately 150mg. For particulate samples, homogenize the material before measurement (e.g., by crushing, mortar and pestle, etc.).

[0123] The starting weight of the calibration standard should be selected within the expected measurement range of the test sample. Before use, the standard must be dried at 105°C for 2 hours. Select the standard based on the expected sulfur content of the sample:

[0124] For calibration of test samples with sulfur content not exceeding 2.5%, the following calibration materials are used:

[0125] 502-671 coal standard, approximately 1% sulfur; from Leco

[0126] 502-422 white oil standard, approximately 2% sulfur; from Leco

[0127] For calibration of test samples with sulfur content exceeding 2.5%, the following calibration materials are used:

[0128] sulfanilic acid standard, from Eltra

[0129] Calibration is completed by calculating a calibration line containing at least four calibration points. The test results are evaluated and calculated using LECO instrument software.

[0130] D75 mod or mode mod – The particle size distribution of modified silica after ultrasonic depolymerization was determined using a disc centrifuge.

[0131] The sample to be analyzed was dispersed in a propane-1,2-diol / water mixture, depolymerized by ultrasonic energy, and then separated according to particle size in a disc centrifuge: the analysis was performed on a CPS Instruments DC24000 disc centrifuge.

[0132] Set the disc centrifuge to a speed of 20,000 rpm.

[0133] The preparation involved filling a running disc centrifuge with a density gradient of a sucrose solution containing propane-1,2-diol and Nonidet (Nonidet P40, from AppliChem GmbH), and covering it with a dodecane top layer.

[0134] The sugar solution concentrations in this study ranged from w=8% to w=24% sucrose. The density gradient was divided into 10 levels:

[0135] 24.0% / 22.2% / 20.4% / 18.7% / 16.9% / 15.1% / 13.3% / 11.6% / 9.8% / 8.0%.

[0136] To this end, two sugar solutions with the following compositions were prepared:

[0137] High-density solution: 24% sucrose aqueous solution + 0.2% nonidet

[0138] Low-density solution: 8% sucrose aqueous solution + 24% propane-1,2-diol + 0.2% nonidet

[0139] Inject 1.8 ml of sugar solution for each density level into a disc centrifuge, starting with the highest concentration. To do this, mix the two sugar solutions together in the desired proportion using a dosing syringe, as follows:

[0140]

[0141]

[0142] Finally, inject 0.5 ml of dodecane.

[0143] Weigh 0.10 g (±0.01 g) of the sample and place it in a 30 ml quick-lid vial. Add 15 ml of a solution consisting of 24% propane-1,2-diol and 0.2% nonidet in softened water.

[0144] With the aid of clamps, the filled quick-cap vials were secured in a cooling bath (Julabo F12). The cooling bath had been pre-equilibrated to 5°C (±1°C). An ultrasonic probe (from Hielscher; UP200S with S14 ultrasonic electrodes) was placed, with the ultrasonic electrodes submerged 5.5 cm in the vial, and measurements were taken from the upper edge of the quick-cap vial. The sample was continuously sonicated at 100% power for 15 min.

[0145] program

[0146] During measurement, the following parameters should be set in the instrument's dedicated software:

[0147] Sample parameters (decimal places in the software description are indicated by dots, not commas):

[0148] Maximum diameter: 5.0 micrometers

[0149] Minimum diameter: 0.02 micrometers

[0150] Particle density: 2.11 g / ml

[0151] Particle refractive index: 1.46

[0152] Particle absorption: 0.001K

[0153] Aspheric coefficient: 1.0

[0154] Calibration standard parameters:

[0155] Peak diameter: xxx micrometers 1 )

[0156] Half-peak width: 0.15 micrometers

[0157] Particle density: 1.385 g / mL 1 )

[0158] Fluid parameters:

[0159] Fluid density: 1.075 g / ml

[0160] Fluid refractive index: 1.3706

[0161] Fluid viscosity: 2.0 cps

[0162] Presentation parameters:

[0163] Display Mode: Weight

[0164] X-axis scale: Logarithmic

[0165] Note: 1 - Enter the calibration standard according to the manufacturer's instructions (e.g., PVC reference standard from CPS Instruments).

[0166] The measurement wavelength was set to 470nm.

[0167] In each case, inject 0.1 ml of the standard or sample suspension. Perform dual determination (including dispersion) on each sample to be analyzed.

[0168] result

[0169] The raw data curves (absorption measurements) were used to determine the weight distribution using the instrument's dedicated software. They are reported below:

[0170] Mode mod (Unit: nm) - The most common particle size, corresponding to the x-axis value of the maximum value of the logarithmic distribution function;

[0171] D 75,mod (75% by weight of particle size, in nm) - 75% of the particle size distribution is higher than

[0172] The particle size at that value (from the cumulative curve);

[0173] D75 mod or mode mod – The particle size distribution of depolymerized silica was determined using ultrasonic energy via a disc centrifuge.

[0174] The samples to be analyzed were depolymerized in an aqueous suspension using ultrasonic energy, and then separated according to particle size in a disc centrifuge: the analysis was performed on a CPS Instruments DC24000 disc centrifuge.

[0175] The measurements were performed at 20,000 rpm using a method similar to that used for modified silica.

[0176] When deviations occur, a density gradient is established in 9 levels using sugar solutions of the following concentrations (between w=8% and w=24% sucrose):

[0177] 24% / 22% / 20% / 18% / 16% / 14% / 12% / 10% / 8%

[0178] Inject 1.6 ml of sugar solution for each density grade into a disc centrifuge, starting with the highest concentration. Finally, inject 0.5 ml of dodecane.

[0179] Before the test, the sample was ultra-finely ground using a Fritsch grinder (Pulverisette 14 with an 80 μm sieve). 0.75 g (±0.05 g) of the grinding material was weighed and placed in a 30 ml quick-lid vial, and 15 ml of softened water was added.

[0180] When deviation occurs, set the following parameters in the instrument's dedicated software for measurement:

[0181] Sample parameters (decimal places in the software description are indicated by dots, not commas):

[0182] Maximum diameter: 5.1 micrometers

[0183] Minimum diameter: 0.02 micrometers

[0184] Particle density: 2.0 g / ml

[0185] Particle refractive index: 1.44

[0186] Particle absorption: 0.001K

[0187] Aspheric coefficient: 1.1

[0188] Calibration standard parameters:

[0189] Peak diameter: xxx micrometers 2 )

[0190] Half-peak width: 0.2 micrometers

[0191] Particle density: 1.385 g / mL 1 )

[0192] Fluid parameters:

[0193] Fluid density: 1.045 g / ml

[0194] Fluid refractive index: 1.344

[0195] Fluid viscosity: 1.2 cps

[0196] Presentation parameters:

[0197] Display Mode: Weight

[0198] X-axis scale: Logarithmic

[0199] 2) It depends on the specific calibration standard.

[0200] The evaluation method is similar to that used for modified silica.

[0201] Drying loss – determined according to DIN EN ISO 787-2

[0202] The weight loss of a sample heated at 105°C for 2 hours in a drying oven was measured.

[0203] This procedure conforms to DIN ISO 787-2 and the following instructions:

[0204] The weighing bottle (with a flanged cap; approximately 80 mm in diameter and 30 ml in height) is capped and heated at 105°C for approximately 1 hour. After cooling in a desiccator, the cap is reinserted. The weight is accurately measured to 0.01 g using a precision balance. 5-10 g of the sample (weight depends on bulk density) is accurately weighed and spread in a uniform layer at the bottom of the weighing bottle. The weighing bottle is carefully opened and heated in a desiccator at (105±2)°C for 2 hours (including heating the cap).

[0205] Carefully seal the weighing bottle with the cap, place it in a desiccator to cool, and reweigh it precisely to 0.01g.

[0206] calculate

[0207]

[0208] E = starting weight, in grams.

[0209] A = Final weight, in grams

[0210] pH – pH of silica according to DIN EN ISO 787-9

[0211] a. Determination method for unmodified silica

[0212] This procedure conforms to DIN ISO 787-9 and the following instructions:

[0213] Before weighing, the particulate sample material is crushed using a mortar and pestle.

[0214] Prepare a 5% (m / m) aqueous suspension of the sample to be analyzed. Softened water (DMPA) is used for this purpose.

[0215] Before measuring the pH value, stir the sample suspension on a stirrer for at least 5 minutes.

[0216] The pH value was measured using a previously calibrated pH meter (Metrohm, model 780, with pH electrode 6.0228.000 (Metrohm)).

[0217] b. Determination method for modified hydrophobic silica

[0218] This procedure conforms to DIN ISO 787-9, and the descriptions and deviations are as follows:

[0219] Before weighing, the particulate sample material is crushed using a mortar and pestle.

[0220] Weigh 5g of the sample to be analyzed. Add 40ml of softened water (DM) and 60ml of methanol (PA) to it.

[0221] Before measuring the pH value, stir the sample suspension on a stirrer for at least 5 minutes.

[0222] The pH value was measured using a previously calibrated pH meter (Metrohm, model 780, with pH electrode 6.0228.000 (Metrohm)).

[0223] c. Determination method for modified hydrophilic silica

[0224] This procedure conforms to DIN ISO 787-9 and the following instructions:

[0225] Before weighing, the particulate sample material is crushed using a mortar and pestle.

[0226] Prepare a 5% (m / m) aqueous suspension of the sample to be analyzed. For this purpose, boiled softened water (DMPA) is used.

[0227] Before measuring the pH value, stir the sample suspension on a stirrer for at least 5 minutes.

[0228] The pH value was measured using a previously calibrated pH meter (Metrohm, model 780, with pH electrode 6.0228.000 (Metrohm)).

[0229] TAR – Particle wear determined by brittleness test of unmodified silica

[0230] For wear determined by particle brittleness testing, both fine and coarse fractions of silica are removed, and a fraction of 3.15–5.00 mm is used. The particle fractions are subjected to repeated mechanical stress for 30 minutes in a rotating brittleness chamber (e.g., ERWEKATAR 220 with brittleness drums on both sides). Subsequently, the resulting fine fractions are removed using a 500 μm sieve. The mass variation (in %) corresponds to particle wear.

[0231] The abrasion test was repeated twice. The 3.15–5.00 mm particle fraction was sieved carefully by hand (using an analytical sieve with a metal mesh, ISO 3310-1, 200 mm aperture diameter – nominal aperture sizes 500 μm, 3.15 mm, and 5.00 mm, and a sieve disc). This excluded fine and very coarse particles. (5.00 ± 0.1) g of the 3.15–5.00 mm fraction was accurately weighed on an analytical or precision balance. A representative portion of the sample must be collected. The sample was added to a brittle drum; it was then mounted on an abrasion tester. The instrument was run at 65 rpm for 30 minutes. Subsequently, the material was quantitatively applied to a 500 μm sieve, and any adhering fine particle fractions were removed by moderate stirring / movement for 3–5 seconds. The particles were then accurately weighed again on a precision or analytical balance to a final weight of 0.01 g.

[0232] evaluate

[0233]

[0234] Wear: Wear measured by particle brittleness test, in percentage.

[0235] E: The initial weight of the 3.15-5.00mm (or 1.00-3.15mm) fraction obtained from sieving, in grams.

[0236] A: Residue after stress application and removal of fine particles, in grams.

[0237] The measurement result is the average of two separate measurements and is reported as a percentage, rounded to one decimal place.

[0238] TAR mod – Particle wear determined by brittleness test of modified silica

[0239] Similar to the TAR determination of unmodified silica described above, however, the fine and coarse fractions of silica were removed, and the 1.00-3.15 mm fraction was used.

[0240] Residue on ignition – The residue on ignition of silica is determined according to ISO 3262-1 or ASTM D 6740.

[0241] a. Determination of unmodified silica (ISO 3262-1)

[0242] The total water content (physical and chemically combined) of precipitated silica was determined by igniting it in a furnace at 1000°C for 2 hours, thereby determining the content of all volatile components (loss on ignition) and calculating the residue on ignition.

[0243] Measurement Procedure

[0244] Using an analytical balance with an accuracy of ±0.1 mg, approximately 500 mg of silicon dioxide was weighed in each of two porcelain crucibles or molten crucibles with the aid of a scraper. The crucibles, together with the silicon dioxide, were then ignited in a furnace at (1000±50) °C for (120±5) min.

[0245] After ignition, place the crucible in a desiccator with a suitable desiccant to cool for approximately 1.5–2.0 hours, and reweigh it using an analytical balance. Repeat the determination twice.

[0246] evaluate

[0247] First, calculate the loss on ignition (IL) based on the dry matter content. (干燥) ):

[0248]

[0249] IL (干燥) Loss on ignition of a substance dried at 105℃ for 2 hours is expressed in percentage (%).

[0250] m E The mass of silicon dioxide weighed is in grams.

[0251] m A The mass of silicon dioxide after ignition is measured in grams.

[0252] DL: Drying loss at 105℃ for 2 hours, expressed as a percentage.

[0253] Based on the loss on ignition (IL) of the original material (原始) The following calculation is based on the ignition residue (IR) of the original material. (原始) ):

[0254] IL (原始) =IL (干燥) *(100-DL) / 100 (unit: %)

[0255] therefore

[0256] IR (原始) =100%-DL-IL (原始) (Unit: %)

[0257] Therefore, the drying loss was determined by the method of "Determination of drying loss according to DIN EN ISO 787-2" (see above).

[0258] b. Determination of modified silica (ASTM D 6740)

[0259] The residue is mainly composed of SiO2, which forms during the decomposition of silanes and the calcination of silica. This method conforms to ASTM D 6740.

[0260] Weigh out approximately (0.5-1.0) g. 1 The sample to be analyzed is placed in a pre-calcined crucible with an accuracy of 0.1 mg. Approximately 2 ml of 90% sulfuric acid is added, and the crucible is carefully tilted to mix.

[0261] Place the crucible in a preliminary ashing apparatus (model: SVR / E, controllable up to 2500 W) and gradually heat from 10% (=250 W). After removing the acid (the sample is almost dry), heat the preliminary ashing apparatus to its maximum temperature. Then, place the crucible in a preheated muffle furnace (1000 °C) for 2 hours. If the ash remains gray or black after this, further calcine at 1000 °C for 2 hours. Cool the crucible in a desiccator and weigh accurately to 0.1 mg.

[0262] _________________________

[0263] 1 The starting weight should be selected such that the residue mass is greater than 100 mg.

[0264] calculate

[0265] The calculation of the ignition residue R is as follows:

[0266]

[0267] m1 = Sample weight, in grams

[0268] m2 = mass of residue, in grams.

[0269] (Loss on ignition V (in %) is expressed as V = 100 - R)

[0270] PV(V80,3.7-80nm,140°),IF(140°,dV / dR),IS(90%,140°,dV / dR),R min (90%, 140°, dV / dR) - Determination of pore radius and pore volume based on mercury porosimetry according to DIN 66133.

[0271] The pore size, corresponding pore volume, and pore distribution of pressurized silica samples were determined within a pressure range of 0.03 to 420 MPa. Measurements were performed using a Micromeritics AutoPore IV9520 according to DIN 66133.

[0272] Deviating from DIN 66133, the silica sample was pressure-treated prior to measurement. This was done using a SpecacAtlas manual 15-ton hydraulic press. 1g of sample was added to a Specac Ltd. tablet mold with an inner diameter of 13mm, and pressure of 1t was applied as indicated. This load was maintained for 1 minute. The sample was then depressurized and dried in a drying oven at 105±2℃ for 2 hours.

[0273] For measurements, the prepared sample was weighed and placed in a Micromeritics Model 16 penetrometer. Approximately 330 mg was weighed, accurate to 0.001 g. The penetrometer was then gradually evacuated to 50 μm Hg in the low-pressure port of the instrument and held at this pressure for 5 min. Subsequently, the penetrometer was filled with mercury first in the low-pressure port and then in the high-pressure port to 420 MPa, and the measurement curve (pressure / volume curve) was recorded. The Autopore instrument was operated according to the Micromeritics operating instructions and was software-controlled. Each measurement was calibrated using a blank measurement of the penetrometer. The overall measurement range was 0.003–420 MPa.

[0274] According to DIN 66133, using standard values, the measurement results are calculated from the measurement curve:

[0275] Contact angle: 140°

[0276] Surface tension: 480 dyn / cm

[0277] Evaluate the following parameters:

[0278] PV (V80, 3.7-80nm, 140°)

[0279] IF(140°, dV / dR)

[0280] IS (90%, 140°, dV / dR)

[0281] R min (90%, 140°, dV / dR)

[0282] Ro-Tap (>150μm; >300μm; >500μm) – Sieve analysis according to Annex F of ISO 5794-1

[0283] Sieve analysis was performed using a rotary sieve separator (Tyler Ro-Tap RX-29 analytical sieve separator with timer switch). The method was performed according to Annex F of ISO 5794-1. For sieve analysis, test sieves with different aperture sizes were stacked together (analytical sieves with metal mesh, ISO 3310-1, nominal aperture size 150 μm, aperture diameter 200 mm; analytical sieves with metal mesh, ISO 3310-1, nominal aperture size 300 μm, aperture diameter 200 mm; analytical sieves with metal mesh, ISO 3310-1, nominal aperture size 500 μm, aperture diameter 200 mm). After sieving for 5 minutes, the corresponding fractions were weighed.

[0284] The sieving column is installed in a Ro-Tap sieving machine. The order from bottom to top is as follows: sieve tray, 150 μm sieve, 300 μm sieve, and 500 μm sieve. Gently homogenize the sample before analysis. Weigh (100 ± 1) g, accurate to 0.01 g, on a precision balance, place it in a beaker, and quantitatively transfer the sample onto the top sieve (500 μm). Perform Ro-Tap sieving using a tapper (5 min ± 5 s). After sieving, remove the sieving column and weigh the fractions on the 150 μm, 300 μm, and 500 μm sieves.

[0285] calculate

[0286] Ro-Tap > 500 μm (in %) = (A 500 ·100%) / E

[0287] as well as

[0288] Ro-Tap > 300 μm (in %) = (A 300 ·100%) / E

[0289] and

[0290] Ro-Tap > 150 μm (in %) = (A 150 ·100%) / E

[0291] A 500 = Residue on a 500μm sieve, in grams

[0292] A 300 = Residue on a 300μm sieve, in grams

[0293] A 150 = Residue on a 150μm sieve, in grams

[0294] E = starting weight, in grams.

[0295] With ISO Deviation from Appendix F of 5794-1

[0296] In cases of deviation from the standard, according to the test instructions, sieves with aperture sizes of 150μm, 300μm, and 500μm are used.

[0297] DOA absorption – DOA absorption determined according to ISO 19246

[0298] For performance testing, 12.50 ± 0.02 g of sample was introduced into the kneader chamber of a Brabender Absorptometer E with an extended function / evaluation unit. Then, dioctyl adipate (e.g., ethyl adipate) was metered at a rate of 4 mL / min by constant kneading. DOA). Kneader speed was 125 rpm. The procedure used the raw data curve to calculate a polynomial. The 70% value of the maximum torque of this polynomial was used to determine the DOA absorption based on the raw material, in ml / (100g). Determination was performed according to ISO 19246.

[0299] For silica particles, the determination is performed using a 1.00–3.15 mm particle size fraction, which must be prepared in advance by sieving using an appropriate sieve.

[0300] The following settings should be made in the measuring instrument software:

[0301] Test conditions

[0302] Metering rate (burette): 4.0 ml / min

[0303] Kneader speed: 125 min-1

[0304] Temperature: 23.0℃

[0305] evaluate

[0306] Experiment ended

[0307] Torque threshold: 100mNm

[0308] End: 60 seconds after the maximum value

[0309] Torque limit: 10,000 mNm

[0310] polynomial

[0311] Start at 50% of maximum torque.

[0312] End: 20 seconds after the maximum value

[0313] By using appropriate reference materials with different DOA absorptions, it is possible to... The software was used to separately standardize the kneader. Based on the established standardization function (linear equation Y = a*x + b), and based on the original substance (unit: ml / (100g)), the DOA absorption (standardized) is expressed as 70% of the maximum torque value, taken from the measurement report. Example

[0314] The reference silica used is the following silica or modified silica (Table 1). The unit phf (filler percentage) refers to the weight parts of the additive based on 100 parts by weight of silica:

[0315] Silica 1 is from Evonik Resource Efficiency GmbH. 9100GR.

[0316] Silica 2 was prepared according to Example 1 in EP 1525159 B1.

[0317] The silica 3 is from Evonik Resource Efficiency GmbH. 7000GR.

[0318] Silica-4 is from Solvay. Premium 200MP.

[0319] Silica-5 is from Solvay. 1165MP.

[0320] Silica 6 was prepared according to Example 4 in EP 0901986 B1.

[0321] Silica 7 is from Ciptane, PPG Industries Ohio, Inc. TM .

[0322] 8+9 silica is from PPG Industries, Ohio, Inc. 400 and 458.

[0323] Silica 10 was prepared according to Example 1 in WO2014033300 A1.

[0324] Silica-11 is from Evonik Resource Efficiency GmbH. 8113GR.

[0325] Silicon dioxide 12 is based on Example 4 of EP 0901986 B1, using 5 phf Si modified.

[0326] Silicon dioxide 13 is based on Example 4 of EP 0901986 B1, using 10 phf Si modified.

[0327]

[0328] The silica of the present invention, 14-21, was prepared by initially mixing starting silica and additives in a conveying screw and then drying in a Henschel mixer (Thyssen's Henschel FM 40 fluid mixer). For Examples 14-21, 3000 g of starting silica prepared according to Example 4 of EP 0901986 B1 was used. Additives were used according to the formulation (Table 2). The mixer was preheated to 100°C. After adding the silica / additive mixture, it was dried in the Henschel mixer at 2500 rpm for 4 min.

[0329] In Examples 14, 16, 18 and 20, the modified silica was then compacted in a rolling mill.

[0330] Table 2 shows the compositions of modified silica according to the invention. The unit phf (filler percentage) refers to the weight parts of the additives per 100 parts by weight of silica: Si It is the bis[(3-triethoxysilyl)propyl] disulfide of Evonik Resource Efficiency GmbH. NXT is Momentive's (EtO)3Si-(CH2)3-SC(O)-C7H 15 .

[0331] Table 2

[0332]

[0333] Table 3 shows the analytical data of the modified silica according to the invention.

[0334]

[0335] Modified silica 22-29 according to the invention was prepared in a rotary flash dryer. Base silica for modification was prepared according to Example 4 of EP0901986B1 and Example 1 of EP 1525159 B1. The resulting filter cake was conveyed to the rotary flash dryer via a conveying screw. The additive was added to the conveying unit via a conduit before metering the resulting mixture into the drying chamber. Optionally, the dried silica was granulated.

[0336] The silicone oil used is Dow Xiameter. TM PMX-200Silicone Fluid is a polydimethylsiloxane with a viscosity of 50 cSt.

[0337] Table 4 shows the analytical data for modified silica.

[0338] Table 4

[0339]

[0340] Rubber property inspection

[0341] The materials used in the rubber compound are listed in Table 5. Another reference silica used is from Evonik Resource Efficiency GmbH. VN 3GR.

[0342] The formula is shown in Table 6.

[0343] Table 5: List of materials used in the examples

[0344]

[0345] Table 6: Formulation of S-SBR / BR mixtures

[0346] Phase 1 SSBR 96.3 96.3 96.3 96.3 96.3 96.3 96.3 BR 30 30 30 30 30 30 30 The modified silica 15 of the present invention 90.6 - - - - - - The modified silicon dioxide 21 of the present invention - 91.4 - - - - - The modified silicon dioxide 19 of the present invention - - 90.6 - - - - The modified silicon dioxide 17 of the present invention - - - 90.6 - - - ULTRASIL VN 3GR - - - - 80 - - 5% silicon dioxide - - - - - 80 - Silicon dioxide 6 - - - - - - 80 Si 266 - - - - 6.4 6.4 6.4 ZnO 2.0 2.0 2.0 2.0 2.0 2.0 2.0 stearic acid 2.0 2.0 2.0 2.0 2.0 2.0 2.0 Oil 8.75 8.75 8.75 8.75 8.75 8.75 8.75 wax 2.0 2.0 2.0 2.0 2.0 2.0 2.0 PPD 2.0 2.0 2.0 2.0 2.0 2.0 2.0 TMQ 1.5 1.5 1.5 1.5 1.5 1.5 1.5 Phase 2 Phase 1 batch of materials DPG 2.5 2.5 2.5 2.5 2.5 2.5 2.5 Phase 3 Phase 2 batches of materials CBS 1.6 1.6 1.6 1.6 1.6 1.6 1.6 sulfur 2.14 2.2 2.14 2.14 2.14 2.14 2.14 TBzTD 0.2 0.2 0.2 0.2 0.2 0.2 0.2

[0347] Rubber mixtures were prepared using a GK 1.5E closed mixer from Harburg Freudenberger Maschinenbau GmbH (Table 7).

[0348] Table 7: Preparation of S-SBR / BR mixtures

[0349]

[0350]

[0351] The physical test results of the rubber mixtures or their vulcanization products specified in this paper are listed in Table 8. The vulcanization products were prepared by heating the untreated mixture from stage 3 at 130 bar and 165°C for 15 min. The rubber mixtures were measured using the methods described in Table 9.

[0352] Table 8: Physical test results of the rubber mixtures and their vulcanization products specified in this paper.

[0353]

[0354] As can be clearly seen from Table 8, the compounds (1-4) according to the present invention exhibit improved processing characteristics compared to the reference mixtures (5-7), manifested as reduced Mooney viscosity (mixing stages 2 and 3) and reduced minimum torque ML (mixing stage 3). The conversion times of t10% and t90% after mixing stage 3 also demonstrate an extended processing window with optimized vulcanization conversion. Furthermore, compared to the reference mixtures (5-7), the mixtures (1-4) according to the present invention show improved elongation at break while maintaining the same tensile strength. The vulcanized mixtures according to the present invention exhibit superior dynamic properties compared to the references (5-7), while also possessing good abrasion resistance (mixtures 1, 3, and 4) and dispersion quality.

[0355] Table 9:

[0356]

Claims

1. Modified silicon dioxide, characterized in that... It has the following physicochemical parameters: 。 2. The modified silicon dioxide according to claim 1, characterized in that... The modified silica is modified precipitated silica.

3. The modified silica according to claim 1, characterized in that... Ro-Tap > 300 µm is > 50%.

4. The modified silica according to claim 1, characterized in that... Drying loss < 4.5% by weight.

5. The modified silica according to claim 1, characterized in that... pH > 6.

3.

6. The modified silica according to claim 1, characterized in that... TAR mod Value > 1%.

7. The modified silica according to claim 1, characterized in that... The residue after burning is 70%-95%.

8. The modified silica according to claim 1, characterized in that... The IF value obtained by measuring the pore size of pressurized Hg is < 170 Å.

9. The modified silica according to claim 1, characterized in that... The IS value obtained by measuring the pore size of pressurized Hg is < 79 ml / (100 g).

10. The modified silica according to claim 1, characterized in that... The PV value at V80, 3.7-80 nm, and 140° is < 0.86 ml / g.

11. A method for preparing modified silica according to claim 1, characterized in that... At the inlet of the drying unit, silica is mixed with at least one additive selected from the following: an aqueous sulfur-containing alkoxysilane emulsion, a polysiloxane, a mixture of sulfur-containing alkoxysilane and polysiloxane, or a mixture of sulfur-containing alkoxysilane and anionic polyether, and then supplied to the drying unit, wherein the polysiloxane is a modified polydimethylsiloxane having a polyether phosphate group, an alkyl ester group or a polyether group.

12. The method for preparing modified silica according to claim 11, characterized in that... The sulfur-containing alkoxysilane is a bis[(3-triethoxysilyl)propyl] disulfide or (EtO)3Si-(CH2)3-SC(O)-C7H 15 .

13. The method for preparing modified silica according to claim 11, characterized in that... The reaction is carried out in a Henschel mixer or a rotary flash dryer.

14. A rubber compound comprising: (A) Rubber or rubber mixtures, and (B) At least one of the modified silicas according to claim 1.

15. A method for preparing the rubber compound according to claim 14, characterized in that... The rubber or rubber mixture, the modified silica according to claim 1, and other optional rubber additives are mixed in a mixing unit.

16. Use of the rubber compound according to claim 14 in the manufacture of cable sheaths, hoses, drive belts, conveyor belts, roller covers, tires, shoe soles, gasket elements and damping elements.

17. The use according to claim 16, wherein the tire is a pneumatic tire.

Citation Information

Patent Citations

  • Process for the production of a hydrophobic precipitated silica with a high degree of whiteness and extremely low moisture absorption

    DE10138491A1

  • hydrophobic, non-annealed precipitated silica with a high degree of whiteness

    DE10138492A1

  • Easily dispersible precipitated silica

    EP0901986B1

  • High-surface precipitation silicic acids

    EP1525159B1

  • Novel method for preparing precipitated silicas, novel precipitated silicas and their uses, in particular for strengthening polymers

    WO2014033300A1